2014
DOI: 10.1093/brain/awu138
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondrial origin for frontotemporal dementia and amyotrophic lateral sclerosis through CHCHD10 involvement

Abstract: Mitochondrial DNA instability disorders are responsible for a large clinical spectrum, among which amyotrophic lateral sclerosis-like symptoms and frontotemporal dementia are extremely rare. We report a large family with a late-onset phenotype including motor neuron disease, cognitive decline resembling frontotemporal dementia, cerebellar ataxia and myopathy. In all patients, muscle biopsy showed ragged-red and cytochrome c oxidase-negative fibres with combined respiratory chain deficiency and abnormal assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
437
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 402 publications
(460 citation statements)
references
References 43 publications
19
437
3
1
Order By: Relevance
“…Little is known, however, about the physiological role of CHCHD10 (7). Most studies have focused on characterizing CHCHD10's effects in mitochondria by testing the effects of pathogenic mutations in a cell culture system (8,9,14). These studies have suggested that CHCHD10 affects stability of mitochondrial cristae (9, 14), COX activity (7), formation of mitochondrial networks (8), stability of mitochondrial DNA, and apoptosis (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known, however, about the physiological role of CHCHD10 (7). Most studies have focused on characterizing CHCHD10's effects in mitochondria by testing the effects of pathogenic mutations in a cell culture system (8,9,14). These studies have suggested that CHCHD10 affects stability of mitochondrial cristae (9, 14), COX activity (7), formation of mitochondrial networks (8), stability of mitochondrial DNA, and apoptosis (14).…”
mentioning
confidence: 99%
“…domaincontaining 10 (CHCHD10) and CHCHD2 (MNRR1) are homologous proteins with 58% sequence identity and belong to the twin CX 9 C family of proteins that mediate cellular stress responses. Despite the identification of several neurodegeneration-associated mutations in the CHCHD10 gene, few studies have assessed its physiological role.…”
mentioning
confidence: 99%
“…In human cells, the activity of the soluble IMS-localized (CX 9 C) 2 motif-carrying protein 238 CHCHD10 ( Table 1), which is enriched in cristae junctions, impacts mitochondrial 239 ultrastructure through hitherto poorly understood mechanisms [98]. A missense mutation 240 (S59L) in CHCHD10 that is associated with frontotemporal dementia (FTD) and amyotrophic 241 lateral sclerosis (ALS) [98,99] causes respiratory deficiencies accompanied by mitochondrial 242 dysgenesis and fragmentation in patient fibroblasts [98] (Table 2).…”
mentioning
confidence: 99%
“…A missense mutation 240 (S59L) in CHCHD10 that is associated with frontotemporal dementia (FTD) and amyotrophic 241 lateral sclerosis (ALS) [98,99] causes respiratory deficiencies accompanied by mitochondrial 242 dysgenesis and fragmentation in patient fibroblasts [98] (Table 2). CHCHD10 and its 243 paralogue CHCHD2, which are encoded by genes localized on chromosomes 22q11.23 and 244 7p11.2, respectively, have emerged as a result of gene duplication during the evolution from 245 yeast to man [49].…”
mentioning
confidence: 99%
“…198,199 Exome sequencing in parent-case offspring trios has already been employed for the investigation of de novo mutations in SALS. [200][201][202] To this end, de novo mutations have been found in genes encoding chromatin regulators, including the neuronal chromatin remodeling complex (nBAF) component SS18L1 (also known as CREST).…”
Section: Twin Studies In Alsmentioning
confidence: 99%